Pengaruh Asimetri Informasi dan Tingkat Disclosure Terhadap Biaya Ekuitas Dengan Kepemilikan Manajerial Sebagai Variabel Moderating (Studi Empiris Pada Perusahaan Manufaktur Di Bursa Efek Indonesia) - Ratri Nurjanati; Ahmad Rodoni (Esensi: Jurnal Bisnis dan Manajemen, 2015)
The objective of this research, the first to analyze the effect information asymmetric toward the cost of equity, the second to analyze the effect level of disclosure toward the cost of equity, and the third to analyze the effect the managerial ownership toward the cost of equity of the manufacturing industry which are listed in Indonesian Stock Exchange (IDX) in 2010-2013. This research used samples of 35 manufacturing industry which are listed in Indonesian Stock Exchange. The sample selection method used purposive sampling method. The statistical testing were used by Partial Least Square (PLS. )The result of this research indicate that (1) information asymmetry have influences significanctly toward the cost of equity, (2) the level of disclosure don’t have influences significantly toward the cost of equity, and (3) the managerial ownership have influences significantly toward the cost of equity.DOI: 10.15408/ess.v5i2.2339